Influence of thermal conditions on the reliability and parameters of devices - A. .. Ataev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The cooling systems for semiconductor integrated circuits with high degree of integration of microelectronic circuits and electronic devices with high density thermal power based on dielectric fluid and heat pipes are proposed.